Efetividade e sensibilidade com uso de géis clareadores experimental e comercial à base de peróxido de carbamida - Santana, Rosemary Soares de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This clinical study assessed tooth sensitivity (SD) and the effectiveness of home bleaching as well as the color relapse after the use of based on commercial carbamide peroxide gels (CP) containing potassium nitrate and fluoride (PF) and experimental gels (EX) also containing sodium tripolyphosphate (STP). A hundred patients, who underwent tooth whitening treatment, were divided randomly into 5 groups (n = 20/groups): 1) 10% carbamide peroxide experimental gel PF Mint (EX10); 2) 20% carbamide peroxide experimental gel PF Mint (EX20); 3) 10% commercial carbamide peroxide gel (Opalescence 10% Mint PF) (OP10); 4) 20% commercial carbamide peroxide (Opalescence 20% Mint PF) (OP20); 5) placebo 0% carbamide peroxide gel PF mint (PL). Bleaching was performed on a single arch of each patient for 2 hours during 14 days. In order to evaluate the color, it was used spectrophotometer, photographic analysis, and Vita 3D Master Bleachedguide in the periods: initial, 7 and 14 days after the start of the treatment and 30 days after the end to verify the color stability. The SD was daily evaluated, according in the following grades: absence, mild, moderate, substantial and severe. The results were analyzed by ANOVA (repeated measures) for measurement by spectrophotometer, Kruskal-Wallis and Dunn tests, 5% of significance to sensitivity to visual scale. Comparisons of shade guide the color analysis showed p < 0.05, and sensitivity to 0.0482 < 0.05. The whitening gel OP10 promoted better color results and minor sensitivity compared to the EX10. And the EX20 group showed greater lightening action with same level of sensitivity as the OP20 group. It was concluded that the groups OP10 and EX20 promoted the best results regarding the whitening with the smallest rate of sensibility when compared to the groups with the same concentrations and there was STP influence on the whithening effectiveness

Este estudo clínico avaliou a sensibilidade dentária (SD) e a efetividade do clareamento caseiro, bem como a reincidência de cor após uso de géis, à base de peróxido de carbamida (CP) comerciais contendo nitrato de potássio e fluoreto (PF) e experimentais (EX) contendo também tripolifosfato de sódio (STP). Cem pacientes foram submetidos ao tratamento de clareamento dental, sendo divididos aleatoriamente em 5 grupos (n = 20 / grupo): 1) Peróxido de carbamida PF Mint gel experimental 10% (EX10); 2) Peróxido de carbamida PF Mint gel experimental 20% (EX20); 3) Peróxido de carbamida comercial 10% (Opalescence PF 10% Mint) (OP10); 4) Peróxido de carbamida comercial 20% (Opalescence PF 20% Mint) (OP20); 5) Gel placebo de peróxido de carbamida (PL). Realizou-se clareamento em uma única arcada de cada paciente, por 2 horas/dia, durante 14 dias. Para análise da cor utilizou-se análise por espectrofotômetro, análise fotográfica e pela escala Vita Bleachedguide 3D Master nos períodos: inicial, 7 e 14 dias após o início do tratamento e 30 dias após o término para verificar a estabilidade da cor. A SD foi avaliada diariamente qualificando a intensidade da dor em: ausência, discreta, moderada, considerável e severa. Os resultados foram analisados pelos testes ANOVA (medidas repetidas) para mensuração por espectrofotômetro, teste Kruskal-Wallis para sensibilidade e Dunn para escala visual, significância 5%. A análise de cor visual apresentou p < 0.05, e a sensibilidade 0.0482 < 0.05. O gel de clareamento OP10 promoveu melhores resultados de cor e menor sensibilidade comparado ao EX10. O grupo EX20 apresentou maior ação clareadora com mesmo nível de sensibilidade que o grupo OP20. Concluiu-se que os grupos OP10 e EX20 promoveram os melhores resultados quanto ao clareamento com menor índice de sensibilidade quando comparados com os grupos de mesmas concentrações e que o STP influenciou na efetividade do clareamento
Keywords: Materiais dentários; Dentina - Sensibilidade; Clareadores dentários; Dental materials